Biochemical effect of a histidine phosphatase acid (phytase) of Aspergillus japonicus var. Saito on performance and bony characteristics of broiler - Maller, Alexandre; Oliveira de Quadros, Thays Cristina [UNESP]; Junqueira, Otto M. [UNESP]; Grana, Alfredo Lora; Lima Montaldi, Ana Paula de [UNESP]; Alarcon, Ricardo Fernandes; Jorge, Joao Atilio; Polizeli, Maria de Lourdes T. M. (Springer, 2016)
Phytases are enzymes that hydrolyze the ester linkage of phytic acid, releasing inositol and inorganic phosphate. The phytic acid (phytate) is a major form of phosphorus in plant foods. Knowing that diet for animal of production has the cereal base (corn and soybean), primarily, broilers need for an alternative to use of the phosphate present in these ingredients, since it does not naturally produce the enzyme phytase, which makes it available. The aims of this work was studding the safe supplementation of Aspergillus japonicus var. Saito crude phytase in feeding broilers and check the biochemical effect on performance and bones of these animals. The enzymatic extract did not have aflatoxins B1, B2, G2 and G1 and zearalenone and ochratoxin, and low concentrations of this extract did not have cytotoxic effects on cells derived from lung tissue. The in vivo experiments showed that the phytase supplied the available phosphate reduction in the broiler feed formulation, with a live weight, weight gain, feed intake, feed conversion, viability, productive efficiency index and carcass yield similar to the control test. Furthermore, the phytase supplementation favored the formation of bone structure and performance of the broilers. The results show the high biotechnological potential of A. japonicus phytase on broiler food supplementation to reduce phosphorus addition in the food formulation. So, this enzyme could be used as a commercial alternative to animal diet supplementation.
Keywords: Biochemical effect; Phytate; Phosphate; Animal diet; Supplementation